Penerapan Metode Pembelajaran dalam Pembelajaran Ekonomi Materi Ketenagakerjaan di Kelas XI SMA Methodist 8 Medan - Adelia Lubis; Agnes Tamba; Krisentia Napitu; Legi Simbolon; Revita Yuni (Universitas Negeri Medan, 2026)
This study aims to analyze the application of learning methods to employment topics in grade XI students at Methodist 8 High School, Medan. The study employed descriptive methods with a qualitative approach through observation and documentation of learning activities. The results indicate that teachers integrated lecture, question-and-answer, discussion, presentation, and assignment methods. The application of various methods improved student participation, communication skills, collaboration, and understanding of employment topics. However, challenges persisted, including a lack of student participation and limited learning time. Therefore, the use of various learning methods needs to be continuously developed to create more active and student-centered learning.